Between realities and virtualities: Mapping information management and knowledge management terms in information studies programs in Portugal and Spain - de Freitas, Maria Cristina Vieira; Leite, Filipa Manuela Ramos Morado; Borges, Maria Manuel; Cabero, Manuela Moro [UNESP] (My University, 2019)
The study deals with the realities/virtualities of the so-called information/knowledge societies. We mapped the curricula of the current programs in Information Studies in Portugal and Spain and analyzed their contents. We identified the presence of the terms “information management” and “knowledge management” and perceived their representativeness. This study followed a qualitative approach with exploratory and descriptive emphases. The literature review was selective. The documentary analysis was based on official documents, published on the Web and carefully contrasted. We identified the institutions of the Portuguese and Spanish education systems and examined the curricula and syllabi of the programs. The results show varying degrees of incidence/coincidence of terms in both countries and the different programs that were analyzed. Comparatively, the terms are more frequent in the Spanish syllabi than in the Portuguese ones. The term “information management” is the most frequent one in both countries, while they present low level of coincidence of these terms We concluded that there is a need for future studies to deepen the screening and analysis of the content of these programs, crossing the results with the perceptions of students, admissions, and graduates about the real/virtual repercussions of the inclusion of these topics in their education and professional activities.
Entre realidades y virtualidades: Mapeo de términos de gestión de información y gestión de conocimiento en programas de estudios de información en Portugal y España
Entre realidades e virtualidades: Mapeamento dos termos gestão da informação e gestão do conhecimento em planos de estudos de informação em Portugal e em Espanha
Keywords: Course curricula; Information management; Knowledge management; Portuguese higher education; Spanish higher education